2012
DOI: 10.1177/0148607111430507
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome in Neonatal Short Bowel Syndrome Using Parenteral Fish Oil in Combination With ω‐6/9 Lipid Emulsions

Abstract: Parenteral fish oil in combination with ω-6/9 lipid emulsions was associated with improved outcome in premature neonates with SBS. When used instead of traditional soybean-based emulsions, this mixed lipid emulsion may facilitate intestinal adaptation by increasing the IFALD-free period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 50 publications
(79 reference statements)
1
46
0
Order By: Relevance
“…The 2:1 ratio of soybean oil to fish oil found in SMOF is apparently not sufficient to entirely prevent IFALD. Angsten et al 26 reported the outcome of 20 neonates, all of whom were started on PN with soybean‐based LE that was switched to a combination of fish oil (Omegaven) and ω‐6/9 LE (ClinOleic, Baxter, Maurepas, France) in a 1:1 ratio for IFALD. They showed that parenteral fish oil–based LE in combination with ω‐6/9 LE for premature infants with short bowel can reverse cholestasis and ultimately lead to reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The 2:1 ratio of soybean oil to fish oil found in SMOF is apparently not sufficient to entirely prevent IFALD. Angsten et al 26 reported the outcome of 20 neonates, all of whom were started on PN with soybean‐based LE that was switched to a combination of fish oil (Omegaven) and ω‐6/9 LE (ClinOleic, Baxter, Maurepas, France) in a 1:1 ratio for IFALD. They showed that parenteral fish oil–based LE in combination with ω‐6/9 LE for premature infants with short bowel can reverse cholestasis and ultimately lead to reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis persisted after FO treatment, despite improvements of cholestasis. Angsten G et al (JPEN 2012) 22 In a case series of 20 neonates with short bowel disease. Values expressed as multiples of the upper limit of the normal range.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Adding to the cost, investigators may continue FO until PN discontinuation even if direct hyperbilirubinemia has resolved. To date, the longest median follow-up on liver function reported on children who have received FO is 16 months 9 . There is no data on patients whose FO has been discontinued prior to intestinal adaptation, and limited follow-up on subjects after adaptation 2-10 .…”
Section: Introductionmentioning
confidence: 99%